Topographic correlation between macular superficial microvessel density and ganglion cell-inner plexiform layer thickness in glaucoma-suspect and early normal-tension glaucoma. Issue 1 (2nd April 2019) - Kim, Jin-Soo; Kim, Young Kook; Baek, Sung Uk; Ha, Ahnul; Kim, Yong Woo; Jeoung, Jin Wook; Park, Ki Ho
Abstract : Background/Aims: To investigate the topographic relationship between macular superficial microvessel density (SMD) and macular ganglion cell-inner plexiform layer (GCIPL) thickness in eyes with glaucoma-suspect (GS) and early normal-tension glaucoma (NTG). Methods: A total of 86 eyes of 86 patients with early NTG (standard automated perimetry mean deviation >−5.5 decibels) and a total of 25 eyes of 25 patients with GS were retrospectively reviewed. All of the subjects underwent optical coherence tomography (OCT) and OCT angiography (OCTA) scan. On the OCTA scan images, macular SMD was analysed by customised software. Results: In GS and patients with early NTG, macular GCIPL thickness showed significant correlations with macular SMD in the superotemporal (ST), inferotemporal (IT) and inferoinferior (II) sectors ( r = 0.191, 0.373 and 0.346 for ST, IT and II sector, respectively). Additionally, circumpapillary retinal nerve fibre layer (RNFL) thickness and macular SMD showed significant correlations between the ST sector of the macula and the 1, 9 clock-hour peripapillary regions and between the IT and II sectors of the macula and the 6, 7, 8 clock-hour peripapillary regions. The IT sector macular SMD showed fair diagnostic power (area under the receiver operating characteristic curve [AUROC] = 0.758) and showed high diagnostic power when combined with IT sector macular GCIPL thickness (AUROC=0.954). Conclusions: Sectoral macular SMD showed topographic correlations with macular GCIPL thickness and circumpapillary RNFL thickness in patients with GS and early-stage NTG. Macular SMD analysis is potentially useful in the clinical evaluation of early glaucoma.